Controversies over the concept of validity - Rytel, Jolanta (Studia Psychologica: Theoria et praxis, 2021)
In the article the key changes which have occurred in conceptualization of validity are considered. Validity is currently defined in term of the degree to which a proposed interpretation of test scores is justified by evidence and theory (American Educational Research Association, American Psychological Association, National Council on Measurement in Education [AERA, APA, NCME], 2007, p. 31). Five types of validity evidence are described, and problems with the integrations of various strands of evidence in sound validity argument are discussed. Usefulness of Kane’s argument-based approach to validity referring to informal logic and the structure of the argument introduced by Toulmin is stressed in the article. There is also emphasized the lack of uncontroversial definition of validity.